Läroplansimplementering och korstryck i fritidshemmets arbete - Boström, Lena; Berg, Gunnar (Educare, 2018)
In Swedish leisure-time-centers, there is a daily activity for about half a million children. It is characterized by a complexity including, for example, changes in steering documents, lack of an accentuated pedagogy and a changing profession. Against this background, this study focuses on leisure-time-teachers’ perceptions of curriculum implementation and possible impact in the leisure-time-center education practice. The empirical data consists of individual interviews, focus groups and field studies. In the study, theories of curriculum didactics and organizational theory are combined. As an analytical concept, curriculum implementation and cross pressures are used. The result shows that the values ​​and tasks that the leisure-time-teachers emphasize in relation to the steering documents are social skills, professional ambivalence and the status of leisure-time-centers. Strategies personnel use is high leadership structure, reactive confirmation of steering documents and traditional leisure-time activities. Restrictions in the professional practice are the low status of activities in leisure-time-centers compared with traditional school activities, lack of time for implementation, "schooling" and unclearness in the steering documents’ descriptions. This means that several stressful cross pressure are experienced in different ways at work, which complicates the realization of the curriculum’s intentions. I svenska fritidshem pågår i en daglig verksamhet för cirka en halv miljon barn. Den präglas av en komplexitet omfattande exempelvis förändringar av styrdokument, brist på en accentuerad pedagogik och en förändrad profession. Mot denna bakgrund fokuserar denna studie på fritidspedagogers uppfattningar om läroplansimplementering och eventuell genomslagskraft i den fritidspedagogiska praktiken. Empirin består av individuella intervjuer, fokusgrupper och fältstudier. I studien flätas teorier om läroplansdidaktik och organisationsteori samman. Som analytiska begrepp används läroplansimplementering och korstryck. Resultatet visar att värden och uppgifter som pedagogerna betonar i relation till styrdokumenten är sociala färdigheter, professionell ambivalens samt fritidshemmets status. Strategier personalen använder är hög ledarskapsstruktur, reaktiv bekräftelse av läroplansskrivningar samt traditionella fritidshemsverksamheter. Begränsningar är fritidshemsverksamhetens låga status i jämförelse med traditionell skolverksamhet, brist på tid för implementering, ”skolifiering” samt oklarheter i styrdokumentens innehållsbeskrivningar. Därmed upplevs flera stressande korstryck i olika bemärkelser i arbetet, vilket försvårar realisering av läroplanens intentioner.